FAUNA IKAN AIR TAWAR DIPULAU BUTON PROVINSI SULAWESI TENGGARA [Freshwater ichthyofauna in Buton Island, Southeast Sulawesi] - A. H. Tjakrawidjaja (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2006)
As a relatively isolated part of Indonesia, Sulawesi has an interesting biogeography and a high proportion of endemic species. Freshwater and estuarine fish of Buton Island, in south eastern Sulawesi, was surveyed and collected in June 2003. A total of six sites were sampled, either by electrofishing or by seine netting. The survey tentatively identified 31 species from 22 genera within 12 families. Members of the Gobiidae and related families dominated the collections ielO species (32.3%). Some specimens that could not be identified using existing keys may be new to science. While hill stream communities included fish adapted to live in strong currents, the lower reaches of rivers contained species capable of surviving high water temperatures and low oxygen tensions. River estuaries had the highest species diversity and contained juveniles of many marine forms that use the estuary as a nursery area. In rivers running through intact rainforest, a few species were found to specialize on feeding on invertebrates that fall onto the water surface. Samples from these environments included the undescribed species of gobies (Gobiidae).